PENGARUH MINAT, KEMANDIRIAN, DAN SUMBER BELAJAR TERHADAP PRESTASI BELAJAR SISWA PADA MATA PELAJARAN IPS KELAS VII SMP NEGERI 5 UNGARAN - Hadi, Syamsu; Farida, Fitriana Salis (Dinamika Pendidikan, 2012)
The objectives of this study were to determine 1) the influence of studentsâ learning interest toward studentsâ achievement on social studies at the 7th Grade students in SMP Negeri 5 Ungaran partially. 2) The influence of studentsâ learning independence toward studentsâ achievement on social studies at the 7th Grade students in SMP Negeri 5 Ungaran partially. 3) The influence of learning resources toward studentsâ achievement on social studies at the 7th Grade students in SMP Negeri 5 Ungaran partially. 4) The influence of interest, independence, and learning resources toward studentsâ achievement on social studies at the 7th Grade students in SMP Negeri 5 Ungaran simultaneously. The populations of the study were all students at the 7th Grade students in SMP Negeri 5 Ungaran, they were 216 students. The sampling technique was cluster proportional random which found 70 students as the samples. Then, data were collected by questionnaires, interviews and documentation and analyzed by multiple linear regression analysis, F test and t-test. The results of the study showed that: 1) there was positive influence of studentsâ learning interest toward studentsâ achievement on social studies at the 7th Grade students in SMP Negeri 5, it was proved byÂ  t- 2.772> t table 1.997. 2) There was positive influence studentsâ learning independence toward studentsâ achievement on social studies at the 7th Grade students in SMP Negeri 5 Ungaran, it was proved by t 2.037 > t table 1.997. 3) There wasÂ  positive influence of learning resources toward studentsâ achievement on social studies at the 7th Grade students in SMP Negeri 5 Ungaran, it was proved by t 2.262Â  t> t table 1.997. 4) There was a significant influence of studentsâ interest, independence, and learning resources toward studentsâ achievement on social studies at the 7th Grade students in SMP Negeri 5 Ungaran, it was proved by the constant value was 51.909.